2012
DOI: 10.1002/lary.23320
|View full text |Cite
|
Sign up to set email alerts
|

Airway stem cells

Abstract: Epithelial remodeling is a part of our natural defense mechanisms, and includes migration, proliferation, and differentiation of epithelial cells, as well as the interactions between epithelial and stromal cells. It is not yet possible to distinguish between cause and effect during epithelium remodeling, and are there no clear roles for the many factors involved in respiratory infectious and inflammatory diseases due to a lack of critical information about epithelial cell responses. Most reported data are from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Dysregulation of airway epithelial basal cells can cause the aberrant remodeling process (e.g., basal cell hyperplasia, goblet cell hyperplasia, and squamous metaplasia)213. Our previous study found that p63 expression levels were higher in epithelium from patients with NP than in healthy controls, and it was associated with the severity of epithelial hyperplasia4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dysregulation of airway epithelial basal cells can cause the aberrant remodeling process (e.g., basal cell hyperplasia, goblet cell hyperplasia, and squamous metaplasia)213. Our previous study found that p63 expression levels were higher in epithelium from patients with NP than in healthy controls, and it was associated with the severity of epithelial hyperplasia4.…”
Section: Discussionmentioning
confidence: 98%
“…Emerging evidence has demonstrated that epithelium from NP patients plays an important role in the pathogenesis of NP. In patients with NP, the epithelium is attacked by various stimulants, leading to acute or chronic injury and dysregulated restitution followed by aberrant remodeling2. Our previous studies reported a down-regulation of activator protein 1 (AP1) and its related genes (e.g., COX2, IL6, and epidermal growth factors) was associated with the damage of epithelial structure3; while up-regulation of p63 in basal cells was implicated in the epithelial hyperplasia in NP4.…”
mentioning
confidence: 99%
“…Basal cells have been identified as stem/progenitor cells able to self-renew and differentiate into other epithelial cell types [ 26 ]. Stem/progenitor cells have a central role in tissue homeostasis, repair and regeneration of mucous membrane including the nasal mucosa [ 27 ]. The cellular pathogenesis of nasal polyps is related to a homeostatic imbalance between the reduction in proliferation of nasal epithelial stem/progenitor cells [ 28 ], and the presence and differentiation of mesenchymal stem/progenitor cells (MSCs) [ 29 ].…”
Section: Intra-cellular Signaling Transduction Mechanisms Underlyimentioning
confidence: 99%
“…3 This supports the claim that the nasal epithelium is exposed to all environmental agents including infectious agents (such as viruses, bacteria, and fungi), allergens, and air contaminants before the bronchial epithelium, thus protecting the lower airway. 3,4 However, some infectious agents, allergens, and air contaminants may still reach the lower airway. Therefore, both the upper and lower airways must have a functionally adequate epithelial barrier to ensure our survival.…”
Section: Introductionmentioning
confidence: 99%